(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Thrombocytopenia is a critical hematological abnormality presenting a significant diagnostic challenge, requiring precise differentiation between peripheral platelet destruction and impaired central bone marrow production. This study provides a comparative evaluation of advanced laboratory parameters in patients with Primary Immune Thrombocytopenia (ITP) and secondary thrombocytopenia associated with hypersplenism (hepatic cirrhosis). A retrospective cross-sectional study was conducted involving 120 participants: 45 patients with ITP, 45 with cirrhosis-associated thrombocytopenia, and 30 healthy controls. Comprehensive peripheral blood analyses focused on advanced platelet indices, including Mean Platelet Volume (MPV) and Immature Platelet Fraction (IPF). Statistical evaluation utilized the Student’s t-test and chi-square analysis. The results revealed profound differences in platelet morphology despite similar degrees of absolute thrombocytopenia in the pathological groups. The ITP cohort exhibited a significantly elevated MPV (11.8 ± 1.2 fL) and IPF (18.5 ± 2.4%) compared to the secondary thrombocytopenia group (MPV 9.2 ± 0.8 fL; IPF 6.2 ± 1.5%, p < 0.001), reflecting intense compensatory megakaryopoiesis in response to autoimmune peripheral destruction. Using a cut-off of MPV > 10.5 fL yielded a diagnostic sensitivity of 84.4% and specificity of 88.0% for identifying ITP. Routine assessment of advanced platelet indices offers a highly reliable, non-invasive, and cost-effective method for differentiating the etiology of thrombocytopenia, significantly optimizing diagnostic algorithms and minimizing the immediate need for invasive bone marrow aspirations in regional clinical settings.